Full Genome Sequence of Giant Panda Rotavirus Strain CH-1 - Guo, Ling (American Society for Microbiology, 2013)
We report here the complete genomic sequence of the giant panda rotavirus strain CH-1. This work is the first to document the complete genomic sequence (segments 1 to 11) of the CH-1 strain, which offers an effective platform for providing authentic research experiences to novice scientists.